2011
DOI: 10.1293/tox.24.215
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Goiter in Cynomolgus Monkeys Following Administration of the Antithyroid Drug Thiamazole at High Doses to Dams During Pregnancy

Abstract: To evaluate morphologic alterations in the thyroid gland in the second generation in cynomolgus monkeys, pregnant dams were exposed to high doses of thiamazole. In Experiment A, dams received thiamazole intragastrically via a nasogastric catheter from gestation day (GD) 50 to GD 150 or on the day before delivery. Initially, the dose level was 20 mg/kg/day (10 mg/kg twice daily); however, the dose level was subsequently decreased to 5 mg/kg/day (2.5 mg/kg twice daily), since deteriorated general conditions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In all surviving infants, the weights of thyroids in the treated groups were three-to four-fold heavier than those in the control group; yet no histopathological abnormalities were seen in these organs at necropsy. It has been reported that oral treatment of maternal monkeys with thiamazole during GD 50 to 150 at an initial dose of 20 mg/kg per day induced newborn deaths due to tracheal compression and suffocation from extreme enlargement of the thyroids at birth, although the dose level was later reduced to 5 mg/kg per day (Yoshikawa et al 2011). The thyroids of fetuses receiving 5 mg/kg per day during the middle or late gestational period also showed histopathologic abnormalities such as hyperplasia and hypertrophy of the follicular epithelium consisting of crowded pedunculated structure (Yoshikawa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all surviving infants, the weights of thyroids in the treated groups were three-to four-fold heavier than those in the control group; yet no histopathological abnormalities were seen in these organs at necropsy. It has been reported that oral treatment of maternal monkeys with thiamazole during GD 50 to 150 at an initial dose of 20 mg/kg per day induced newborn deaths due to tracheal compression and suffocation from extreme enlargement of the thyroids at birth, although the dose level was later reduced to 5 mg/kg per day (Yoshikawa et al 2011). The thyroids of fetuses receiving 5 mg/kg per day during the middle or late gestational period also showed histopathologic abnormalities such as hyperplasia and hypertrophy of the follicular epithelium consisting of crowded pedunculated structure (Yoshikawa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that oral treatment of maternal monkeys with thiamazole during GD 50 to 150 at an initial dose of 20 mg/kg per day induced newborn deaths due to tracheal compression and suffocation from extreme enlargement of the thyroids at birth, although the dose level was later reduced to 5 mg/kg per day (Yoshikawa et al 2011). The thyroids of fetuses receiving 5 mg/kg per day during the middle or late gestational period also showed histopathologic abnormalities such as hyperplasia and hypertrophy of the follicular epithelium consisting of crowded pedunculated structure (Yoshikawa et al 2011). These Yoshikawa's observations suggest that fetal thyroids in the treated groups had ever been hyperplastic and possessed microscopic abnormalities in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation